2010
DOI: 10.1159/000285281
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Type of Chromosomal Abnormalities in Childhood Acute Lymphoblastic Leukemia Patients in Kuwait: A Six-Year Retrospective Study

Abstract: Objective: To characterize the frequency of genetic profiles in pediatric acute lymphoblastic leukemia (ALL) patients in Kuwait. Subjects and Methods: This review presents the general cytogenetic characteristics of 164 pediatric patients diagnosed as having ALL in a 6-year period. Chromosomal and fluorescence in situ hybridization studies were made on bone marrow aspirates at diagnosis and during different stages of the disease. Results: Recurring aberrations, observed in 123 (75%) patients, included hyperdipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
3
2
0
Order By: Relevance
“…Especially, B-lineage ALL is more frequent, accounting for 85% of childhood ALL and 75% of adult ALL (WHO, 2008). However, the incidence of chromosomal abnormalities was higher than previously reported studies (Foristier et al, 1997;Mehdipour et al, 2003;Gimidene et al 2008), similar results (Perez-Vera et al, 2001;Al-Bahar et al, 2010) and lower than some studies (Chang et al, 2006;Kwon et al, 2009;Braekeleer et al, 2010). In our study, the bone marrow cultures for nine patients either yielded no metaphases or the quality of the chromosomes was too poor with clumped metaphases, which is commonly known in most of the ALL cases (Petkovic et al, 1996) and the percentage of diploid karyotype (25.8%) presently tended to decrease compared to the earlier years, likely attributable to technical progress such as improvement of culture conditions, cell synchronization, and the introduction of integrated FISH screening method may have led to a higher incidence rate of chromosomal abnormalities in our study similar to previous studies (Hashem, 2012).…”
Section: Discussionsupporting
confidence: 63%
“…Especially, B-lineage ALL is more frequent, accounting for 85% of childhood ALL and 75% of adult ALL (WHO, 2008). However, the incidence of chromosomal abnormalities was higher than previously reported studies (Foristier et al, 1997;Mehdipour et al, 2003;Gimidene et al 2008), similar results (Perez-Vera et al, 2001;Al-Bahar et al, 2010) and lower than some studies (Chang et al, 2006;Kwon et al, 2009;Braekeleer et al, 2010). In our study, the bone marrow cultures for nine patients either yielded no metaphases or the quality of the chromosomes was too poor with clumped metaphases, which is commonly known in most of the ALL cases (Petkovic et al, 1996) and the percentage of diploid karyotype (25.8%) presently tended to decrease compared to the earlier years, likely attributable to technical progress such as improvement of culture conditions, cell synchronization, and the introduction of integrated FISH screening method may have led to a higher incidence rate of chromosomal abnormalities in our study similar to previous studies (Hashem, 2012).…”
Section: Discussionsupporting
confidence: 63%
“…A lower incidence of hyperdiploidy was found in elder patients compared with younger, which was statistically significant when compared with diploid and hyperdiploid group (p<0.05 and p<0.0001 respectively). This was in agreement with the previous reports [2,15,31] , indicating the highest frequency of hyperdiploidy between ages of 2 and 7, which could be associated with a good outcome. In addition, we found a group of patients with T cell phenotype, who showed a positivity for CALLA antigen, suggesting further molecular studies such as cytogenetic in this group.…”
Section: Discussionsupporting
confidence: 94%
“…All of our control samples showed a single diploid pick in their DNA content histograms with a DI=1, as it was expected. The percent of hyperdiploid cases among our patients was 45% which was higher than previous reports [17] , but nearly comparable with another investigation in middle east population reporting a percentage of 41% [15] suggesting a regional or race dependent reason. The mean of DI index in our samples was equal to 1.21, which was again higher than previous study which showed a DI greater than or equal to 1.16 [17] .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Myeloproliferative neoplasms (MPN) represent the remaining 10% of cases. Lymphoid disorders: very rare, half of cases being multiple myeloma with the der(1;7) as the sole abnormality (raising the possibility of an underlying MDS), the other half in various lymphoid disorders chronic lymplocytic leukemia (CLL), Burkitt lymphoma/leukemia, follicular lymphoma), most often part of a complex karyotype (Geisler et al, 1997;Hsiao et al, 2005;Al-Bahar et al, 2010). Others: reported in only one case each of bilineage or biphenotypic acute leukemia with a t(9;22) (Sanada et al 2007), sarcoma (Roberts et al, 2008) and carcinoma (Jin et al, 2002) with complex karyotypes and in two cases of aplastic anemia (Kim et al, 2010).…”
Section: Diseasementioning
confidence: 99%